2010
DOI: 10.1002/nav.20417
|View full text |Cite
|
Sign up to set email alerts
|

Threshold incentives over multiple periods and the sales hockey stick phenomenon

Abstract: In this paper we study threshold-based sales-force incentives and their impact on a dealer's optimal effort.A phenomenon, observed in practice, is that the dealer exerts a large effort towards the end of the incentive period to boost sales and reach the threshold to make additional profits. In the literature, the resulting last period sales spike, is sometimes called the hockey stick phenomenon (HSP.) We show that lack of information leads to the HSP and characterize its form over multiple time periods. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Three sources were utilized to identify alternative policies to cope with the hockey stick phenomenon: ideas proposed by the theoretical framework (Bradley & Arntzen, 1999;Buzzell, Quelch, & Salmon, 1990;Chen, 2000;Poddar & Donthu, 2013;Sohoni et al, 2010), ideas suggested by Consumption Ltd executives and scenarios that arose while the study was being carried out. In all, nine different policies were found that were able to eliminate invoicing spikes at the end of the month (see Table 2).…”
Section: Alternative Policiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Three sources were utilized to identify alternative policies to cope with the hockey stick phenomenon: ideas proposed by the theoretical framework (Bradley & Arntzen, 1999;Buzzell, Quelch, & Salmon, 1990;Chen, 2000;Poddar & Donthu, 2013;Sohoni et al, 2010), ideas suggested by Consumption Ltd executives and scenarios that arose while the study was being carried out. In all, nine different policies were found that were able to eliminate invoicing spikes at the end of the month (see Table 2).…”
Section: Alternative Policiesmentioning
confidence: 99%
“…Adapted from Sohoni et al (2010) Increase logistics flexibility Eliminate or reduce the impact of the spike on logistics by increasing production capacity and inventories…”
Section: Alternative Policiesmentioning
confidence: 99%
See 3 more Smart Citations